The elements of power gadgets, guns, and the struggle for a sustainable future in the rare metal age - Abraham, David S. (Yale University Press, 2015)
Our future hinges on a set of rare metals that few of us have even heard of. In this eye-opening book, a natural resource strategist reveals the critical importance of these transformative elements to our technological lifestyle and the consequences of our reliance upon them, including geopolitical instability and environmental degradation. To see our growing dependency, you need only look at your smartphone: cerium buffs the glass; indium allows your screen to respond to touch; terbium makes images more vibrant; and lithium helps it store energy. Abraham provides readers with a front-row seat to the life of these metals, tracing the paths of these high-tech elements through a dozen countries from the mine to our pockets. But it's not just smartphones that rely on these metals; they are the building blocks of modern society because they are critical for nearly all our electronic, military, and "green" technologies. Just as oil, iron, and bronze revolutionized previous eras, so too will these metals. The challenges this book reveals, and the plans it proposes, make it essential reading for our rare metal age.